National Fund of the Republic of Kazakhstan - Where to go from here / Нацфонд Казахстана – куда двигаться дальше? - Jochec (Йохец), Marek (Марек) (National Business KZ, 2016)
On how to invest the sovereign wealth fund of Kazakstan.
Keywords: SWF; NFRK; sovereign wealth fund; National Fund of the Republic of Kazakhstan; investment